Enantioselective total synthesis of (2S,3R,4R)-D-xylo-phytosphingosine from substituted azetidin-2-one - Pandey, Ganesh; Tiwari, Dharmendra Kumar (Tetrahedron Letters, 2009)
Enantiomerically pure (2S,3R,4R)-D-xylo phytosphingosine is synthesized in 36% overall yield in seven steps from known beta-lactam (8) derived from D-mannitol triacetonide. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: beta-lactam; Enantioselective synthesis; Sphingosine; Wittig reaction